Case Report: The Sexual Experiences of Forensic Mental Health Patients - Brand, Elnike; Ratsch, Angela; Heffernan, Edward (Frontiers in Psychiatry, 2021)
Psychiatrists have an important role in supporting people diagnosed with a major mental health illness to achieving a fulfilling life, which includes a fulfilling sexual life. This paper utilizes case studies to illustrate that the clinical discussions between forensic mental health clinicians and their clients around sexuality and sexual health is overlooked due to the prioritization on people’s mental health care needs. There is a gap in the clinical domain around the acknowledgement and assessment of sexuality and sexual health in mental services. Incorporating sexuality and sexual health into standard clinical assessments will contribute to supporting holistic forensic mental health recovery and rehabilitation.